The Effectiveness of EM4 Addition in the Biofilter Tanks to Reduce the BOD5and COD in the Palm Oil Industry Liquid Waste - Saragih, Azizah Laily; Harahap, Sampe; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractÂ Palm oil liquid waste is rich in BOD5and COD and thus need to be processed before being flown to environment. A study aims to reduce the BOD5and COD in that waste by using the biofilter that was added with EM4 has been conducted in April-May 2019. There were 3 treatments applied, namely the addition of 12 ml, 15 ml and 18 ml EM4 in the anaerob and aerob tanks, 3 replications. The waste was settled for 3 days in the anaerob and 3 days in the aerob tanks. The treated waste was then tested for BOD5 and COD concentrations. The treated waste was also used for rearing Oreocromis niloticus seedlings. Result shown that after being treated using the EM4 enriched biofilter the BOD5 reduced into 138.52- 165.76 mg/L and COD was 282.1- 335.3 mg/L. The survival of Oreocromis niloticusseedlings reared in the treated waste was 87-100 %. The best treatment to reduce the BOD5 was the addition of 12 ml EM4 and the effectiveness was 78%, while that of the COD was 84%. It can be concluded that the addition of EM4 to the biofilter tanks was able to reduce the BOD5 and COD in the palm oil industrial liquid waste.Keyword : Effective Microorganism-4, Oreocromis niloticus, Anaerob tanks, Aerob tanks